Strategies to Overcome Work Stress Employees of PT Permodalan Nasional Madani DKI Jakarta Branch - Deydra Afida; Sri Wahyuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to formulate a strategy to deal with work stress in PNM DKI Jakarta employees. This study used a qualitative method with the data collection technique used was Focus Group Discussion which involved 7 employees of PNM DKI Jakarta Branch. The data analysis technique in this study uses SWOT and QSPM. The results obtained in this study are work stress felt by PNM DKI Jakarta employees as indicated by changes in employee behavior such as reduced appetite and sleep quality. Factors causing work stress on PNM DKI Jakarta employees. The results obtained in this study are that the work stress felt by PNM DKI Jakarta Branch employees is a target set by the company